Peak Height Velocity affects injury burden in circa-PHV soccer players - Monasterio, X.; Gil, S.; Bidaurrazaga-Letona, I.; Lekue, J. A.; Diaz-Beitia, G.; Santisteban, J. M.; Lee, D.-J.; Zumeta-Olaskoaga, L.; Martin-Garetxana, I.; Larruskain, J. (International Journal of Sports Medicine, 2023)
Growth and maturation are potential risk factors for soccer injuries. This research sought to describe how peak height velocity (PHV) affects overall and specific injury burden in circa- and post-PHV elite academy soccer players. Injuries and growth data collected from 2000 to 2020 were studied retrospectively. Longitudinal height records for 124 players were fitted with the Super-Imposition by Translation and Rotation model to calculate PHV (cm/year) and age at PHV. Players were classified according to PHV percentile (fast:=75th; average: 25-75th; slow:=25th) and maturity status (circa- or post-PHV). Overall and specific injury burden (days lost/player-season) and rate ratios for comparisons between groups were calculated based on zero-inflated negative binomial models. Confidence intervals were calculated at the 95% confidence level (CI) and the significance level was set at<0.05. In circa-PHV, players with fast PHV had 2.6 (CI: 1.4-4.8)- and 3.3 (CI:1.3-6.7)-times higher overall burden and 2.9 (CI:1.1-7.1)- and 4.1 (CI: 1.4-15.2)-times higher for growth-related injury burden compared to players with average and slow PHV, respectively. Regular monitoring of growth seems important to detect players at higher risk for being disrupted by growth-related injuries.